Investigation of salmonella in fresh water turtle (Mauremys caspica caspica, Gmelin, 1774) from sewage discharged region into Keban Dam Lake, Elazı? - Özcan, Mikail; Sarieyyü?lu, Mustafa (KAFKAS UNIVERSITY, 2009)
In this study, 6 Salmonella strains were identified from isolated micro-organisms by culture method in 25 freshwater turtle (Mauremys caspica caspica) caught from Koçkale Region of Keban Dam Lake and Haringet strefam (Elazi{dotless}? City sewage discharged area) in july-october. Salmonella isolates was also maked by means of Polymerase Chain Reaction (PCR) technique. According to this result, 6 of 25 turtle were found infected with Salmonella spp. Salmonella spp. could not be isolated from water samples from study area. In conclusion, Salmonella isolated from alive fresh water turtle in Koçkale Region was evaluated that it is threat for human health and fish living in this water.
Elazı? şehir kanalizasyonunun keban baraj gölüne döküldü?ü bölgeden yakalanan tatlı su kaplumba?ası (Mauremys caspica caspica, Gmelin, 1774)'nda Salmonella'ların Araştırılması
Keywords: Elazi{dotless}?; Fresh water Turtle; Keban Dam Lake; PCR; Salmonella